Automating Active Directory administration with Windows Powershell 2.0 - St. Cyr, Ken, 1979- (Serious skills., 2011)
"Why perform a task with dozens of clicks through the Graphical User Interface when you can do it with a single command? Why repeat the same tasks when can automate them? Administrators can work efficiently and effectively by automating both simple and complex administrative tasks using Windows PowerShell cmdlets. In Microsoft Windows Server 2008 R2, the new Active Directory module for Windows PowerShell provides command-line scripting for administrative, configuration, and diagnostic tasks. The Active Directory module enables end-to-end manageability with Exchange Server, Group Policy, and other services, providing a centralized experience for administering your directory service--and automating it. Focused on everyday and frequently-performed tasks, Automating Active Directory Administration with Windows PowerShell 2.0 provides PowerShell solutions for maintaining a Windows Server 2008 R2 environment. Solutions are presented step by step, making it easy for Windows administrators to apply on the job, while the necessary concepts explained and real world examples provided help administrators understand what they are doing"--